2001
DOI: 10.1177/1465116501002002001
|View full text |Cite
|
Sign up to set email alerts
|

Divided Government and International Cooperation in Austria-Hungary, Sweden-Norway and the European Union

Abstract: A growing consensus maintains that divided government makes international cooperation more difficult. This paper takes issue with this claim. While divided government does make treaty ratification more difficult, it also affects the outcome when cooperation breaks down. To understand this effect of divided government, I bring the reversion point into the heart of the analysis of cooperation. If divided government makes this reversion point more unattractive than the reversion point under unified government, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Inspired by the "Paradox of Weakness" (Schelling 1960;Putnam 1988), two level game-analysts predict that status quo-biased domestic actors increase the power of a negotiating member state by credibly tying the hands of the negotiator (Schneider and Cederman 1994;Milner and Rosendorff 1996;Milner 1997;Pahre 1997). Pahre (2001) demonstrates that benefits from domestic constraints not only depend on the preferences of the member states but also on the actor controlling the position of the status quo. Hug and König (2002) found that the status quo-preference of both government and ratifying pivot explain the exclusion of issues from the negotiation table.…”
Section: Veto Players Parliamentary Ratifiers and Popular Votementioning
confidence: 99%
“…Inspired by the "Paradox of Weakness" (Schelling 1960;Putnam 1988), two level game-analysts predict that status quo-biased domestic actors increase the power of a negotiating member state by credibly tying the hands of the negotiator (Schneider and Cederman 1994;Milner and Rosendorff 1996;Milner 1997;Pahre 1997). Pahre (2001) demonstrates that benefits from domestic constraints not only depend on the preferences of the member states but also on the actor controlling the position of the status quo. Hug and König (2002) found that the status quo-preference of both government and ratifying pivot explain the exclusion of issues from the negotiation table.…”
Section: Veto Players Parliamentary Ratifiers and Popular Votementioning
confidence: 99%
“…Her conception of the term differs from the most common definition of "divided government," which refers to different party control of the executive and legislative branches. Various studies Lohmann and O'Halloran, 1994;Hammond and Prins, 1999;Karol, 2000;Pahre, 2001! have debated the effect of divided government in the partisan sense on trade policy, but have yet to reach definitive conclusions as to whether different party control of the two branches increases inter-branch disagreements on trade issues.…”
Section: Explaining Variations In Threat Effectivenessmentioning
confidence: 99%
“…The final possible source of power which we examine is divided government. Two previous two-level game studies (Milner and Rosendorff, 1997;Pahre, 2001), both employing a similar spatial model, demonstrate that divided government under certain conditions can benefit negotiators, while under other conditions it can harm their bargaining stance. Milner and Rosendorff (1997) demonstrate that as a unified government becomes more divided (the negotiator's preference remains relatively integrationist while the legislature becomes less integrationist) the negotiator first witnesses benefits as the negotiated outcome moves closer to his ideal point, but then as the legislature becomes more hawkish, the outcome moves beyond the ideal point of negotiator to a point where it more closely reflects the less integrationist position of the legislature.…”
Section: Divided Governmentmentioning
confidence: 87%